Estradiol-Estrogen Receptor α Mediates the Expression of the CXXC5 Gene through the Estrogen Response Element-Dependent Signaling Pathway - Yaşar, Pelin (Sci Rep, 2016)
17β-estradiol (E2), the primary circulating estrogen hormone, mediates physiological and pathophysiological functions of breast tissue mainly through estrogen receptor α (ERα). Upon binding to E2, ERα modulates the expression of target genes involved in the regulation of cellular proliferation primarily through interactions with specific DNA sequences, estrogen response elements (EREs). Our previous microarray results suggested that E2-ERα modulates CXXC5 expression. Because of the presence of a zinc-finger CXXC domain (ZF-CXXC), CXXC5 is considered to be a member of the ZF-CXXC family, which binds to non-methylated CpG dinucleotides. Although studies are limited, CXXC5 appears to participate as a transcription factor, co-regulator and/or epigenetic factor in the regulation of cellular events induced by various signaling pathways. However, how signaling pathways mediate the expression of CXXC5 is yet unclear. Due to the importance of E2-ERα signaling in breast tissue, changes in the CXXC5 transcription/synthesis could participate in E2-mediated cellular events as well. To address these issues, we initially examined the mechanism whereby E2-ERα regulates CXXC5 expression. We show here that CXXC5 is an E2-ERα responsive gene regulated by the interaction of E2-ERα with an ERE present at a region upstream of the initial translation codon of the gene.